THE IMPACT OF THE COOKED SAUSAGE ENRICHED WITH LACTULOSE AND FOOD FIBERS ON THE MORPHOFUNCTIONAL CONDITION OF THE MUCOUS MEMBRANE OF THE LARGE INTESTINE AND MICROBIOTA (MICROBIOCENOSIS) IN RATS - Leonid S. Kudryashov; Vadim A. Kupriyanov; Ivan T. Scherbakov; Valentina B. Krylova; Tatyana V. Gustova (Теория и практика переработки мяса, 2018)
The researches on the development of medical and medical-preventive food products for people with violation of normal intestinal microflora are presented in the article. It was found that,  the introduction into the formulation of cooked sausage food beet  fibers based on sugar beet, hydrated in a ratio 1:5, in amount 10 %  to weight of mince and lactulose, synthesized from lactose, in  amount 640 mg/kg mince retains the traditional organoleptic  properties of the product. There were carried out comparative  morphometric, histochemical and bacterioscopic studies of boiled  sausage effect without additives and sausage enriched with food  fibers and lactulose on the morphofunctional condition of the mucous membrance of the colon (MMC) of rats. Was shown a significant  height  increase of epithelial surface of epithelium, an increase of frequency mitoses in the epithelium crypts of intestinal glands (from 0.6 ± 0.08 % to 1.1 ± 0.04 %), there is a tendency of increasing  content of goblet ekzokrinnye (from 21.3 ± 5.5 % to 32.4 ± 18.7  %), while the mucosal were intensively produced allopathically  mucus, which indicates the stimulation of sausage, enriched with  lactulose on the functional status of the surface epithelium and intestinal glands of the mucous membrane of the colon. Based on the studies results of the effect of food beet fibers and lactulose,  contained in the ration of rats in large and small intestine were fixed  on order greater amount of bifido- and lactobacteries in comparison  with the animals control group. Same time, it was found that in the  large intestine the number of lactobacilli were much higher in  animals receiving experimental sausage.